Geology and Genesis of the Natalka Gold Deposit, Northeast Russia - Eremin R.A.; Voroshin S.V.; Sidorov V.A.; Shakhtyrov V.G.; Pristavko V.A.; Gashtold V.V. (My University, 1994)
The Natalka lode gold deposit, also known as the Matrosov mine, is located in the Magadan region of northeastern Russia at 61 ° 39' N, 147 ° 50' E. The deposit was discovered in 1943 and production started in 1945. The mine has produced more than 75 metric tons of gold, with an average grade 4 g/metric ton (mt), and has reserves of about 450 mt. The Natalka deposit occurs along the southwestern flank of the Yana-Kolyma metallogenic belt and is confined to the major, NW-trending Tenka fault. The deposit is hosted by Upper Permian carbonaceous sediments, subjected to greenschist metamorphism. The ore zones occur along a Z-shaped, strike-slip fault zone that extends for about 12 to 13 km. In plan view, the ore zones are about 5 km long and 100 to 200 m wide in the northwest portion, 350 to 400 m wide in the central portion, and 600 m wide in the southeast portion of the deposit. The main ore minerals are arsenopyrite and pyrite, which comprise about 95% of the sulfides, along with subordinate pyrrhotite, Co-Ni sulfarsenides, sphalerite, chalcopyrite, galena, native gold, ilmenite, and rutile. Scheelite, tetrahedrite, bournonite, boulangerite, and stibnite occur locally. The major gangue mineral is quartz, with subordinate carbonates, feldspars, chlorite, sericite, kaolinite, montmorillonite, and barite. The total sulfide content of the ore zones ranges from 1 to 3 % , and in places up to 5%. Native gold occurs as large individual grains ranging from 0.1 to 2.0 mm in diameter, or as fine disseminations in arsenopyrite. The average gold fineness is 750 to 790.
Keywords: Natalka; gold